Recommendations for the management of secondary hypogammaglobulinaemia due to B cell targeted therapies in autoimmune rheumatic diseases. (26th December 2018) - Wijetilleka, Sonali; Jayne, David R; Mukhtyar, Chetan; Ala, Aftab; Bright, Philip D; Chinoy, Hector; Harper, Lorraine; Kazmi, Majid A; Kiani-Alikhan, Sorena; Li, Charles K; Misbah, Siraj A; Oni, Louise; et al.
Abstract: Objectives: The association of B cell targeted therapies with development of hypogammaglobulinaemia and infection is increasingly recognized. Our aim was to develop consensus recommendations for immunoglobulin replacement therapy for management of hypogammaglobulinaemia following B cell targeted therapies in autoimmune rheumatic diseases. Methods: A modified Delphi exercise involved a 17-member Taskforce committee, consisting of immunologists, rheumatologists, nephrologists, haematologists, a gastroenterologist, an immunology specialist nurse and a patient representative. The first round identified the most pertinent topics to address in the recommendations. A search string was agreed upon for the identification of publications in PubMed focusing on these areas, for a systematic literature review. Original data was presented from this review to the Taskforce committee. Recommendations from the British Society for Rheumatology, the UK Department of Health, EULAR, the ACR, and the American Academy of Allergy, Asthma, and Immunology were also reviewed. The evidence was discussed in a face-to-face meeting to formulate recommendation statements. The levels of evidence and statements were graded according to Scottish Intercollegiate Guidelines Network methodology. Results: Three overarching principles, eight recommendation statements and a research agenda were formulated. The Taskforce committee voted on these statements, achieving 82–100% agreement for each recommendation. The strength of the recommendations was restricted by the low quality of the available evidence, with no randomized controlled trial data. The recommendations cover risk factors, monitoring, referral for hypogammaglobulinaemia; indications, dosage and discontinuation of immunoglobulin replacement therapy. Conclusion: These are the first recommendations specifically formulated for B cell targeted therapies related to hypogammaglobulinaemia in autoimmune rheumatic diseases. The recommendations are to aid health-care professionals with clinical decision making for patients with hypogammaglobulinaemia.